SETAN DALAM ALQURAN (STUDI KRITIS TENTANG MAKNA SETAN PERSPEKTIF TAFSIR ANWAR Al-TANZIL WA ASRAR AL-TA’WIL) - Ahmad Khoerudin Aziz (UIN Siber Syekh Nurjati Cirebon, 2017)
Satan's identity is still a more attention in the lay and academics. The general definition of Satan is an attraction to be studied academically. The Qur'an is a little offensive to the word Satan with a mysterious creature. Some demonic definitions from the ulama almost met the meeting point, namely Satan is a creature that indicates negative or contrary to the teachings of Allah and His messenger. This study attempts to describe the word demon in the perspective of Anwa's interpretationr al-Tanzi l wa Asrar al-Ta'wil a work of Nasir al-Din Abi Sa'id 'Abdillah bin 'Umar bin Muhammad al-Shairazi al-Baid ulama who was born in Persia in 613 H and died in 691 H / 685 H by taking the word devil both singular and plural meaning and then interpreting the interpretation. Thus, the purpose of this study is to describe the meaning of Satan, both singular and plural meaning of the perspective of Imam al-Baidawi in Anwa's interpretationr al-Tanzil wa Asrar al-Ta'wil.